Clinical implications of positive margins following non‐small cell lung cancer surgery. Issue 3 (30th December 2015) - Predina, Jarrod D.; Keating, Jane; Patel, Neil; Nims, Sarah; Singhal, Sunil
Abstract : Positive margins following pulmonary resection of non‐small cell lung cancer (NSCLC) occur in approximately 5–15% of patients undergoing a curative procedure. The presence of positive margins negatively impacts long‐term outcomes by setting the stage for local and potentially distant disease recurrence. Despite major clinical ramifications, there are very few dedicated reports that examine the implications of positive margins following surgery for NSCLC. Furthermore, published series are typically retrospective studies from single institutions. In this review we analyze published data with special consideration of four pertinent questions: (i) what are the long term outcomes of a positive margin following pulmonary resection?, (ii) is intraoperative margin assessment by frozen section reliable?, (iii) what is the optimal distance of the tumor margin to the surgical margin?, and (iv) should adjuvant chemotherapy and/or radiation therapy be used in the setting of a positive surgical margin? J. Surg. Oncol. 2016;113:264–269 . © 2015 Wiley Periodicals, Inc.